Histopathological diagnosis of ovarian mass (Journal of Pathology of Nepal, 2018)
Background:  Ovarian cysts are common forms of gynecological problems that can be range from physiological cysts to highly aggressive neoplastic lesions. The purpose of this study was to investigate prevalence and frequency of different histopathological patterns of ovarian lesions and their correlation with various parameters in Ahvaz, Iran.Materials and Methods: This is the retrospective study of patients with the ovarian masses at Ahvaz Imam Khomeini Hospital from 2010 - 2015. The relevant clinical details about the patient were retrieved from hospital data. Clinical characteristics of patients such as patient's age, presenting signs and symptoms, histopathological diagnosis, mass type, mass subtype, size of cysts and ovary which is involved were noted. Results: Two hundred sixty seven specimens of ovarian tumor obtained for histopathological examination. Of these, 163(61.0%) were tumor like, 96(36.0%) were benign tumor and 8(3.0%) were malignant. The most common tumor like conditions was Corpus luteum cyst (43.4% cases), among benign and malignant tumors, mature cystic teratoma (17.2% of total) and Epithelial tumors (n=4) were most common. There is a statistically significant positive relation between age and various ovarian masses. (P= 0.002). Histopathological diagnosis wasn't correlated with ovarian involvement.Conclusion: Benign tumors are more common than malignant tumors in all age groups. Germ cell tumors followed by surface epithelial cell tumors are the commonest tumor. Mature cystic teratoma was the most common tumor. Unilaterality is more frequently seen in ovarian tumors and various tumors are seen in various age groups.